Understanding Heterosis, Genetic Effects, and Genome Wide Associations for Forage Quantity and Quality Traits in Multi-Cut Pearl Millet - Govintharaj, Ponnaiah; Maheswaran, Marappa; Blümmel, Michael; Sumathi, Pichaikannu; Vemula, Anil Kumar; Rathore, Abhishek; Sivasubramani, Selvanayagam; Kale, Sandip Mallikarjun; Varshney, Rajeev Kumar; Gupta, Shashi Kumar (Frontiers in Plant Science, 2021)
Two sets of pearl millet hybrids (80 single cross hybrids in Set-I and 50 top cross hybrids in Set-II) were evaluated multi-locationally along with their parents for forage linked traits under multi-cut (two cuts) system. Significant variability was found for forage traits in these single cross and top cross hybrids and their parents. Mean better parent heterosis (BPH) of total dry forage yield (TDFY) was 136% across all the single cross hybrids and 57% across all the top cross hybrids. The mean BPH of In vitro organic matter digestibility (IVOMD) varied from -11 to 7% in single cross hybrids and -13 to 11% in top cross hybrids across cuts. One each of single cross and top cross hybrid outyielded the best commercial check hybrid for both forage yield (TDFY) and quality (CP; Crude protein, and IVOMD) traits. Predictability ratio (PR) was lower than unity for most of the forage traits, indicating predominance of non-additive gene action. Significant and positive associations found between SCA (specific combining ability) effects and BPH for most of the forage traits across cuts in single cross and top cross hybrids indicated contribution of non additive gene effects in heterosis. A diverse panel of 105 forage type hybrid parents (Set-III) genotyped following GBS (Genotyping by sequencing) and phenotyped for CP and IVOMD under multi-cuts for two years identified one stable significant SNP (single nucleotide polymorphism) on LG4 for CP and nine SNPs for IVOMD distributed across all linkage groups except on LG2.